2011
DOI: 10.1149/1.3567653
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Direct-Polish Process on Organic Non-Porous Ultra Low-k Fluorocarbon Dielectric on Cu Interconnects

Abstract: A direct-polish process has applied to the ultra low-k dielectric without the etch stop layer to reduce effective dielectric constant in damascene interconnects. In this study, the direct-polish process on organic non-porous dielectric, fluorocarbon (k=2.2), was demonstrated and an optimum direct-polish process condition was investigated. Mechanical effect, not chemical effect, on fluorocarbon degraded electrical properties by changing of chemical structure of fluorocarbon. A surface plasma treatment of fluoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…It was reported that no change in the structure of fluorocarbon was found after chemical dipping only, such as dipping in slurry in CMP, in our previous study. [31][32][33] Therefore, this finding reveals that the change in the structure of fluorocarbon during DHF cleaning is a possible mechanism occurring after dry etching and this change in structure probably results in the increase in leakage current during post-etching DHF cleaning. To eliminate the effects of post-etching cleaning on the electrical properties, two kinds of post-etching plasma treatment were investigated.…”
Section: Application Of Post-etching Plasma Treatmentmentioning
confidence: 69%
See 1 more Smart Citation
“…It was reported that no change in the structure of fluorocarbon was found after chemical dipping only, such as dipping in slurry in CMP, in our previous study. [31][32][33] Therefore, this finding reveals that the change in the structure of fluorocarbon during DHF cleaning is a possible mechanism occurring after dry etching and this change in structure probably results in the increase in leakage current during post-etching DHF cleaning. To eliminate the effects of post-etching cleaning on the electrical properties, two kinds of post-etching plasma treatment were investigated.…”
Section: Application Of Post-etching Plasma Treatmentmentioning
confidence: 69%
“…On the other hand, NPT of the fluorocarbon film was also proved to protect the film from damage induced by CMP. [31][32][33] Therefore, NPT is critical and practical for the successful integration of the fluorocarbon film into Cu interconnects without dielectric degradation.…”
Section: Application Of Post-etching Plasma Treatmentmentioning
confidence: 99%
“…This result also shows the different mechanism of degradation on electrical properties between porous low-k SiCO:H and non-porous fluorocarbon during direct-polish because of the different structural properties. 12,15,7,[29][30][31][32] Figure 5 summarizes the average leakage currents at the electric field of 1 MV/cm and average dielectric constants of fluorocarbon as a function of over-polishing ratio. In this study, results at an overpolishing ratio of 0% were considered to be the same as that in a conventional polishing process, in which a dielectric protective layer was used to avoid damage on the low-k.…”
Section: Resultsmentioning
confidence: 99%
“…21,22 An advanced brush scrubbing process with a high brush rotation rate (500 rpm) in low applied down-pressure (5.5 kPa) was applied as a post-CMP cleaning process. [23][24][25][26] Finally, a passivation film was deposited, and then an annealing treatment was applied at 150 • C with 1 h. To clarify the impact of the direct-polishing process on the fluorocarbon film, blanket samples were also prepared to evaluate electrical characteristics of fluorocarbon film in a metal-insulator-semiconductor (MIS) structure. For the MIS structure, a 100 nm thick fluorocarbon film with or without post-deposition N 2 plasma treatment (NPT), carried out at a microwave power of 2 kW by N 2 /Ar gases as flow rates of 80/20 sccm for 15 s, was prepared on the 200 mm diameter silicon substrate, followed by a 30 nm thick TiN film formation, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…[16][17][18] The authors have carried out tribological studies of brush scrubbing of fluorocarbon dielectric surfaces in PCC in order to obtain good electrical properties. 19,20) In these studies, the high rotation of the brush leading to increased fluid flow was suggested as the optimum condition to accomplish a satisfactory particle removal efficiency without scratch formation degradation and the electrical properties.…”
Section: Introductionmentioning
confidence: 99%